2019
DOI: 10.1002/hed.25906
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approaches for infratemporal fossa tumor resection: Fifteen years' experience of a single center

Abstract: Background The aims of this study were to report our center's experience with infratemporal fossa (ITF) tumors, to review the treatment modalities and outcomes. Methods Data of patients that underwent resection of ITF tumors in a single tertiary referral medical center were collected and analyzed. Results Sixty‐three patients were included. Sarcoma was the most common pathology (18; 29%). The most common surgical approach was the preauricular‐orbitozygomatic approach (24; 38%), followed by endoscopic, craniofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…The proximity to cranial nerves and other vital structures has made the PPF and infratemporal fossa (ITF) historically challenging to access and resect. Several authors have reported that the rate of negative margin resection of tumors involving the PPF and ITF ranges from 56% to 77% 189–192 . He et al.…”
Section: Resectabilitymentioning
confidence: 99%
“…The proximity to cranial nerves and other vital structures has made the PPF and infratemporal fossa (ITF) historically challenging to access and resect. Several authors have reported that the rate of negative margin resection of tumors involving the PPF and ITF ranges from 56% to 77% 189–192 . He et al.…”
Section: Resectabilitymentioning
confidence: 99%
“…33 This approach has proven effective for resection of malignant pathologies in the infratemporal fossa with overall three-and five-year survival rates for patients of 82% and 66% respectively. 34,35 Modifications with extension to the hairy scalp allow comparable outcomes of the surgical site with the consequence of smaller visible scars. 36 Transfacial approaches are used for resection of anterior skull base pathologies and pathologies within the paranasal sinus.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…2,5,7,8,10,11 Osteosarcomas rarely arise within the pterygomaxillary region/infratemporal fossa. [12][13][14] When involving the mandible and maxilla, the main symptoms of osteosarcoma are pain, swelling, and ulceration. 5 Pain is typically attributable to compression of adjacent nerves or periosteal impingement.…”
Section: Introductionmentioning
confidence: 99%
“…10,16 Treatment of osteosarcoma requires a multidisciplinary approach. 4,8,13,14 Conventional treatment typically consists of neoadjuvant and adjuvant chemotherapy following surgical resection. 1,3,15 While chemotherapy regimens are attributed to increased survival rates, the mainstay of treatment is complete surgical resection.…”
Section: Introductionmentioning
confidence: 99%